PENGARUH AKTIVITAS GENERASI MUDA TERHADAP PENGGUNAAN KATA BAKU DAN TIDAK BAKU PADA PELAJARAN BAHASA INDONESIA - Idawati; Fatimatuzzahra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
In this article describes the results of research on students of UIN Raden Fatah Palembang who can distinguish standard and non-standard languages, it seems that there are still not being able to distinguish these languages, so the purpose of the research is the ability and understanding in distinguishing standard and non-standard languages according to the language,research findings reveal that 85% of students can distinguish standard languages. According to linguistic rules and 15% of students who cannot distinguish non-standard languages. There are many ways to obtain data, including through observation and interviews. according to research results some people still can't understand why this is so because standard Indonesian is needed to make it easier and function as the national language, the language of unity, the pride language of the Indonesian language. In the world of education, Indonesian language subjects are considered to be able to help students to be able to understand and understand the rules of language, therefore students are expected to be able to distinguish them based on the context and purpose of their use not violating Indonesian linguistic norms. the ability of students to recognize and master the appropriate language in accordance with the relevant Indonesian rules. This can help students to be able to distinguish and master vocabulary.